Parental origin of transcription from the human GNAS1 gene. - R. Campbell; Christine Gosden; David T. Bonthron (1994)
Variation in the phenotypic expression of Albright9s hereditary osteodystrophy (AHO) determined by the parent of transmission, suggests that the human Gs alpha gene (GNAS1), in which mutations occur in AHO, may be under imprinted control. GNAS1 is also known to map to a chromosomal region (20q13.11) showing syntenic homology with the imprinted mouse region 2E1-2H3. To establish if GNAS1 is indeed imprinted, we have examined the parental origin of GNAS1 transcription in human fetal tissues. Of 75 fetuses genotyped, at gestational ages ranging from 6 to 13 weeks, 13 heterozygous for a FokI polymorphism in exon 5 of GNAS1 were identified whose mothers were homozygous for one or other allele. RNA from up to 10 different tissues from each fetus was analysed by RT-PCR. In all cases expression from both parental alleles was shown by FokI digestion of RT-PCR products and quantification of the resulting fragments. No tissue specific pattern of expression was discerned in these experiments. If genomic imprinting regulates the expression of the human GNAS1 gene, our data suggest that the effect must either be subtle and quantitative, or be confined to a small subset of specialised hormone responsive cells within the target tissues.